Which factors affect the ability to kneel following total knee arthroplasty? An outpatient study of 100 postoperative knee replacements. (8th November 2019) - Wilding, Christopher P; Snow, Martyn; Jeys, Lee
Background: Kneeling is an important activity of daily living, holding social, religious and occupational value. Following total knee replacement (TKR), many patients report they are unable to kneel or have been advised not to kneel. Methods: We observed 100 consecutive knee replacements in 79 patients attending outpatient clinic at a minimum 5 months post-TKR. The patients were asked to fill out a questionnaire detailing whether they were able to kneel prior to their knee replacement and whether they thought they were able to kneel since their knee replacement. The patients were then asked to kneel on a padded examination couch and then onto a pillow on the floor for 15 s. Degree of flexion achievable was also recorded. Results: Of the knees with patella resurfacing, 78.6% were able to kneel compared to only 45.6% knees with native patellae. Two-tailed Fisher's exact test showed this difference to be statistically significant ( p = 0.001). The χ 2 analysis showed that those patients with an achievable flexion of angle of greater than 100° were significantly more likely to be able to kneel than those with a flexion angle of less than 100° ( p = 0.0148). Comparing posterior cruciate ligament (PCL) retaining against PCL sacrificing implants, there was no statistically significant difference in kneeling ability ( p = 0.541). Conclusion: Kneeling remains an important function in patients undergoing TKR, with patella resurfacing significantly improving the likelihood of a patient being able to kneel.